Improved Quality of Spermatozoa Mice (Mus musculus) Model of Diabetes Mellitus Type 1 After Being Given Cinnamon Bark Methanol Extract (Cinnamomum burmanii Bl.) - Abdul M Ukratalo; Titus Frendi Wedilen; Ian Risaldy Tofure; Dodikrisno Ekaputra Manery; Muhammad Reza Ramadhany (Nusantara Scientific Medical, 2022)
Diabetes mellitus has to do with male fertility, a hormone disorder that affects spermatogenesis. This study aims to determine the effect of cinnamon bark methanol extract (Cinnamomum burmani) on the quality of diabetes mellitus mice spermatozoa. This study used a complete randomized design with 4 treatments and 3 repeats. 22 mice were divided into 4 groups. Mice have injected with streptozotocin dose of 0.1 mL and observed blood sugar levels were, if sugar levels increased, they are given cinnamon bark methanol extract at a dose of 250 mg/kg BB and 500 mg/kg BB, and blood sugar levels are measured. After that, the mice are dissected for observation of spermatozoa's morphology, viability, and motility after administration of the extract. The results showed that cinnamon bark methanol extract at a dose of 250 mg/kg BB and 500 mg/kg BB can reduce the number of abnormal spermatozoa and increase the viability and motility of diabetes mellitus mice spermatozoa. This indicates that cinnamon bark extract as an antioxidant has a positive effect in maintaining structure and development, as well as the function of spermatogenesis cells so that in the presence of these active substances, the number of seed cells that experience developmental failure, degeneration, death due to free radicals can be suppressed or reduced.